Hormones Matter? Association of the Menstrual Cycle With Selective Attention for Liked and Disliked Body Parts - Krohmer, Kerstin; Derntl, Birgit; Svaldi, Jennifer (Frontiers in Psychology, 2019)
Body dissatisfaction is wide spread among women and is considered a risk factor for eating pathology. Therefore, it is clinically relevant to investigate potential influencing factors. While previous research has mainly revealed inconsistent findings for attentional processes in body perception, the present study aimed to investigate the association of menstrual cycle phase with body satisfaction and its perception. In a within subject design, 16 women with a natural menstrual cycle (NC) and 19 women who used hormonal contraception (HC) rated their bodily attractiveness and underwent a 3-minute mirror exposure while their eye movements were recorded at two different times during their cycle (NC: ovulation vs. late luteal phase; HC: mid vs. end of cycle). At ovulation, NC women felt more attractive and gazed less at unattractive body parts in contrast to the late luteal phase, where they felt less attractive and gazed more at unattractive body parts. There was no difference in the gaze pattern for the attractive body parts at ovulation and late luteal phase. Notably, HC women showed a balanced gazed pattern at attractive and unattractive body at both times. The menstrual cycle phase is associated with women’s self-rated attractiveness and selective attention when looking at their own body. It should therefore be taken into account in clinical research addressing body image.